Use of Methotrexate in the Treatment of Juvenile Idiopathic Arthritis - Talukder, Manik Kumar; Rahman, Shahana A (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v31i1.6070 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 22-25